Antipsychotic drugs scavenge radiation-induced hydroxyl radicals and intracellular ROS formation, and protect apoptosis in human lymphoma U937 cells. (4th March 2019) - Zhao, Qing-Li; Ito, Hiroko; Kondo, Takashi; Uehara, Takashi; Ikeda, Masayuki; Abe, Hitoshi; Saitoh, Jun-Ichi; Noguchi, Kyo; Suzuki, Michio; Kurachi, Masayoshi
Abstract: Antioxidant activity has been reported for some atypical antipsychotic drugs; however, the detailed mechanism is not well known. Here, we investigated the effects of atypical antipsychotic drugs on OH radical formation, intracellular reactive oxygen species (ROS), and apoptosis induced by ionising radiation. The reaction rate constants with OH radicals were determined for five antipsychotic drugs as follows, in descending order: olanzapine, aripiprazole, clozapine, haloperidol, and risperidone. Experiments with aminophenyl fluorescein, a fluorescent dye, showed that olanzapine and clozapine could scavenge intracellular ROS. However, experiments with hydroxyphenyl fluorescein showed that only olanzapine inhibited ROS generation. X-irradiation-induced apoptosis in human lymphoma U937 cells was inhibited by clozapine at relatively low concentrations and by olanzapine at higher concentrations. Clozapine inhibited caspase-8 and caspase-3 activation and prevented loss of mitochondrial membrane potential. In contrast, olanzapine inhibited X-irradiation-induced p-JNK activation. Although the atypical antipsychotic drugs used here have relatively high reaction rate constants with OH radicals in aqueous solutions, inhibition of intracellular ROS was not due to OH radical scavenging. In addition, suppression of X-irradiation-induced apoptosis was not directly linked with intracellular ROS scavenging. When apoptosis signalling pathways were studied, clozapine-mediated inhibition of apoptosis was dependent on caspase-3 and caspase-8. In contrast, olanzapine inhibited apoptosis via down regulation of X-irradiation-induced p-JNK. These results suggested that both olanzapine and clozapine have antioxidative and antiapoptotic activities via distinct pathways, and provide useful information for better understanding of drug characteristics.